Application Of Amanah Value To Payment Products At Bank Syariah Indonesia KCP Bandung Moh. Toha - Salsabila Apriliah Koswara; Muhammad Al Mighwar (Al-Fadilah: Islamic Economics Journal, 2023)
Bank Syariah Indonesia (BSI) is one of the Islamic banks in Indonesia whose operational activities comply with the principles of Islamic Sharia and are listed in the law. One of the superior products of Bank Syariah Indonesia is Pawn Gold, which is a service for getting fast money, with an easy process and low maintenance costs. The purpose of this study is to assist customers in understanding and evaluating the level of sharia applied by Bank Syariah Indonesia Kcp. Bandung Moh Toha, so as to provide trust and transparency to customers in transactions. The method used in this study is a qualitative descriptive approach, while the data collection techniques include interviews, observation and documentation. The implementation of the value of trust has been carried out very well, we can see in the work practices of employees who really reflect a high commitment to trust, honesty and decency, as well as upholding religious rules. The employees of Bank Syariah Indonesia Kcp. Bandung Moh Toha makes the value of trust as a foundation in carrying out their daily tasks.